Dual Taks Training Therapy to Reduce Physical Mobility Disorders in Mrs.T with Stroke at Chuzan Hospital Okinawa Japan - Nysa, Cholifatul; Iqomh, Muhammad Khabib Burhanuddin (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stroke causes weakness in the limbs. Weakness experienced by stroke patients can be in the form of hemiplegia, plegia, or paraplegia. Dual task training is a non-pharmacological management of physical mobilisation disorders. Objective: This case study aims to determine the effectiveness of dual task training in patients with impaired physical mobility due to stroke. Method: The type of research in this case study is descriptive. The subject of this case study was Mrs T aged 60 years, a stroke patient with nursing problems of physical mobility disorders in room 2B. Elderly with impaired physical mobility due to stroke will be given dual task training therapy, namely walking using a pyramid A stick in order to maintain balance and increase mobility. To determine the effectiveness of the therapy provided, the author conducted an assessment with the parameters of the breg balance scale (BBS). Results: The results of the initial score before therapy showed a BBS score of 18 points which means that you have to use a wheelchair (wheelchair bound), then after the dual task training therapy action carried out by Mrs T for 3x30 minutes / day carried out for 3 consecutive days, the final result was 32 points which had the interpretation of walking with assistance. Conclusions: The results of the case study show that dual task training therapy is effective for reducing the patient's physical mobility disorder.